Head capsule deformities in Chironomus zealandicus (Diptera: Chironomidae): Influence of site and substrate - Kanapathippillai Jeyasingham; Nicholas Ling (New Zealand Journal of Marine and Freshwater Research, 1997)
The natural incidence of deformities in the larval head capsules of Chironomus zealandicus was investigated at four lake sites in the central North Island, New Zealand, in summer (December 1994) and winter (June 1995). Significant differences were observed between sites and seasons. Individuals from the peat lakes Ngaroto and Hamilton (Rotoroa) had the highest incidence of deformities during summer (78 and 48%, respectively) and these declined significantly in winter (40 and 26%). No seasonal differences were observed in larvae from the two sites chosen in Lake Rotorua. Individuals close to the Hamurana Stream in Lake Rotorua showed the lowest number of malformed head capsules during summer (32%). In order to assess the influence of substrate type, larvae from two different locations were cultured through their entire life cycle in three different substrates. Results overall indicated no clear pattern of substrate effect although some structures may be more sensitive indicators of substrate physico‐chemistry than others. The incidence of deformity tended to decline with successive laboratory culture.